Using Whiteboard Animation to Create Digital Learning Materials: Pengembangan Materi Pembelajaran Digital Menggunakan Whiteboard Animation - Taufiq, Wahyu; Santoso, Dian Rahma; Susilo, Joko (Procedia of Social Sciences and Humanities, 2022)
The advancement of information and communication technology (ICT) in the field of education encourages educators to improve their technology integration skills. This has an impact on school programs, which must be ready to adapt to the times to meet the learning needs of students during the industrial revolution. 4.0. One of the efforts to address the aforementioned challenges is training on the development of digital learning materials using whiteboard animation. The teachers at 'Aisyiyah Midle and Hight Schools (SMP and SMA) in the Lawang sub-district who participated in the activity were able to develop the teaching materials after 50 hours of training that they already possessed by creating material scenarios, which were then transformed into Whiteboard animation. At first, the teachers admitted that it was difficult to understand the selected application, but with perseverance and the guidance of the training materials, all participants were able to create their first whiteboard animation. Furthermore, based on the analysis, it was discovered that the most difficult obstacle encountered by the participants was when adapting to the application and preparation of material development, which was followed by the need to find and develop ideas for the material to be made. The majority of participants are committed to using this application in the creation of additional materials. It is also hoped that similar materials or their development will be obtained in the future.